PENGGUNAAN MEDIA PUZZLE HURUF UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SD NEGERI CIBITUNG - Siti Jakiah; Astri Sutisnawati; Din Azwar Uswatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low initial reading ability of first-grade students at SDN Cibitung. Initial observations show that some students have not been able to recognize letters well, have difficulty combining letters into syllables, and are less motivated in reading activities. The purpose of this study is to improve the initial reading ability of first-grade students at SDN Cibitung through the use of letter puzzle media in Indonesian language learning. The research method used is classroom action research with the Kemmis and McTaggart model which is implemented in two cycles. Each cycle includes the stages of planning, action implementation, observation, and reflection. The research subjects were 20 first-grade students at SDN Cibitung, consisting of 9 male students and 11 female students. Data collection techniques include observation, initial reading ability tests, and documentation. The data analysis technique used is descriptive quantitative analysis. The results of this study are the use of letter puzzle media in learning to read the beginning of grade 1 students of SDN Cibitung can create a more active and interesting learning process for students and can improve students' beginning reading skills as seen from the students' learning completeness in the pre-cycle by 35%, increasing to 60% in cycle 1 and reaching cycle 90% in cycle II. Therefore, the conclusion of this study is that letter puzzle media is proven to be able to improve the beginning reading skills of grade 1 students of SDN Cibitung.